Metodologi Hamka Dalam Pentafsiran Al-Quran: Tumpuan Khusus pada Ayat-Ayat yang Mengandungi Kalimah Pengertian Takwa di Dalam Surah Al-Baqarah, Tafsir Al-Azhar - Muhammad Yusry Affandy, Md. Isa (2012)
This qualitative study examines the Hamka’s approach in performing an exegesis of selected Quranic verses regarding takwa, in the chapter of al-Baqarah. Thus, Hamka’s work on the exegesis of the al-Quran, the Tafsir al-Azhar has been studied. Previous works have discussed major developments in the Quranic exegesis and the various approaches taken by different Islamic scholars in their attempts to study the al-Quran. In addition, other scholarly works from universities as well as public libraries have also been considered. A deductive method was applied to study the usage of takwa terminology in al-Baqarah. An attempt was also made to generally compare the Hamka’s methodology of exegesis with other scholars’ approaches. Furthermore, a descriptive method was used to prepare the overview of knowledge needed in the Quranic exegesis, Hamka’s biography and detailed data as a result of the Hamka’s exegesis of verses regarding takwa in al-Baqarah. Findings have shown that the Hamka’s methodology is compatible with Islam, although it is mainly of his personal understanding and it has few references to other scholars’ views. His opinion on takwa is concurrent with the exegesis of his peers as well as the perspective of authoritative scholars. This study has also established that the Hamka’s exegesis is built on the synthesis of Islamic knowledge, sciences, human psychology, international laws, opinion of medical experts, economics as well as other contemporary knowledge which is particularly beneficial to Muslims of Southeast Asia. This finding has also contributed to consolidate local efforts in the Quranic exegesis, together with the integration of scholarly works left by Hamka.